Transformational leadership and work motivation as predictors of organizational citizenship behavior - Mulyono, Tenang (Implementasi Manajemen & Kewirausahaan, 2021)
The purpose of this study was to determine the direct effect of transformational leadership style (X1) and employee motivation (X2) on organizational citizenship behavior (Y). This study in CV.Putra Karya Agung. Distric of Gresik production unit employee. The number of sample who were taken as many as 92 employees from 120 member of the population by using the slovin method. This study using quantitative method. Data collection used through questionnaires using Likert scale and SPSS versi 21. The analysis method incudes mutiple linier regression.The result show that a significant of individual influenced between transformational leadership style (X1) to organizational citizenship behavior (Y). While employee motivation (X2) do not dignificant of individual influenced to organizational citizenship behavior (Y). And a significant of togeteher influenced between transformational leadership style (X1) and employee motivation (X2) to organizational citizenship behavior (Y).